Zero-Base Budgeting: A Planning, Resource Allocation and Control Tool. - Haselkorn, Michael (The Accounting Review, 1981)
Reviews the book "Zero-Base Budgeting: A Planning, Resource Allocation and Control Tool," by James W. Pattillo.